Investigating the combinatory effect of Sclerocarya birrea with doxorubicin against selected colorectal cancer cell lines - Thembelihle Nxasana; Innocensia Mangoato; Patriciah Masiu; Abhay Mishra; Motlalepula Matsabisa (Drug Target Insights)
Introduction: Colorectal cancer incidences continue to increase annually, worldwide. Herbal plants with antiproliferative properties received research interest as agents that can be adjuvant therapies with chemotherapy drugs to enhance their efficacy and reverse drug resistance.